Pengaruh Likuiditas, Profitabilitas, Solvabilitas, Ukuran Perusahaan, dan Kualitas Audit Terhadap Opini Audit Going Concern (Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2017 – 2021) - Ramadhani, Diah Lestari (LPPM STIE KRAKATAU, 2023)
Abstract This study aims to determine the effect of liquiditys, profitability, solvency, firm size, and audit quality on going concern audit opinion. The sample selection technique in this study used a purposive sampling method and obtained 42 energy sector companies listed on the Indonesia Stock Exchange for the period 2017-2021. The data analysis used in this study was logistic regression analysis using SPSS software version 25. Based on the results of the study, it can be concluded that concluded that liquidity and audit quality have a significant negative effect on going concern audit opinion. Meanwhile, solvency has a positive and significant effect on going-concern audit opinion and firm size has no effect on going-concern audit opinion.